EKSISTENSI PEREMPUAN DALAM NOVEL AKU LUPA BAHWA AKU PEREMPUAN KARYA IHSAN ABDUL QUDDUS (ANALISIS ISI) - Febrizka Alya Rahma; Sumiharti Sumiharti; Harbeng Masni (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research aims to describe the existence of women in aspects of nature, aspects of history, and aspects of myth in the novel Aku Lupa Bahwa Aku Perempuan by Ihsan Abdul Quddus. This research includes a type of qualitative descriptive research described by the expressions/quotations in the collection of the novel Aku Lupa Bahwa Aku Perempuan by Ihsan Abdul Quddus. The data in this research uses primary data in the form of expressions/quotations containing the existence of women included in the novel Aku Lupa Bahwa Aku Perempuan by Ihsan Abdul Quddus. The secondary data is in the form of books. The research results show that there are 64 quotations in the novel Aku Lupa Bahwa Aku Perempuan by Abdul Quddus. There are 15 quotations of nature aspect, 12 quotations of the historical aspect, and 37 quotations of myth aspect